Lareh Nan Bunta: Power Systems and The Concept of Musical Aesthetics in Talempong Basaua in Luhak 50 Koto Minangkabau - Sastra, Andar Indra; Sriwulan, Wilma; Hendri, Yon (Harmonia: Journal of Arts Research and Education, 2018)
The goal of this article is to bring to light lareh nan bunta as a form of representation of the system of democracy – or power – developed by Dt. Nan Sakelap Dunia. The discussion in this paper uses a qualitative method which is backed up by quantitative data. The data was collected through participant observation, interviewing, discussion, and analysis. The analysis was carried out using a descriptive method using theoretical reasoning, with knowledge of aesthetics and art. The results of the research show that conceptually, talempong basaua is a musical reality which represents lareh nan bunta in Luhak 50 Koto Minangkabau. Lareh nan bunta is a synthesis of the influence of power – or dialectic – between lareh kotopiliang (autocracy) and lareh bodicaniago (democracy), each with its own system of leadership. The dualism in the autocratic and democratic systems of power form a balancing power known as lareh nan bunta – a combination of all three existing conceptions. Lareh nan bunta is also reflected in the concept of musical aesthetics in talempong basaua in Luhak 50 Koto Minangkabau. Talempong basaua represents a combination of two musical concepts, namely talempong and the rhythms or irama of dendang (vocal music), which are combined to create a new genre.